Prioritizing development : a cost benefit analysis of the United Nations' sustainable development goals - Lomborg, Bjørn, 1965- (Cambridge : Cambridge University Press, 2018)
This book is a unique guide to making the world a better place. Experts apply a critical eye to the United Nations' Sustainable Development agenda, also known as the Global Goals, which will affect the flow of $2.5 trillion of development aid up until 2030. Renowned economists, led by Bjorn Lomborg, determine what pursuing different targets will cost and achieve in social, environmental and economic benefits. There are 169 targets, covering every area of international development - from health to education, sanitation to conflict. Together, these analyses make the case for prioritizing the most effective development investments. A panel of Nobel Laureate economists identify a set of 19 phenomenal development targets, and argue that this would achieve as much as quadrupling the global aid budget.
Title from publisher's bibliographic system (viewed on 29 May 2018).
Keywords: United Nations -- Environmental policy; Sustainable development -- Cost effectiveness